Determination of minimum inhibitory concentration of third generation cephalosporins and fluoroquinolones on clinical isolates of Pseudomonas aeruginosa - Bite, Bapurao Motiram; Chaudhari, Devendra R.; Wagh, Kailash B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pseudomonas aeruginosa has attracted much attention because of its high incidence of nosocomial infections in recent years. The multidrug resistance of these P. aeruginosa isolates plays an important role in the colonization or infection of chronically hospitalized patients. There is continued search for alternative drugs, such fluoroquinolones, and the third generation cephalosporins. The objective of present study was to test the susceptibility of the clinical isolates of P. aeruginosa to antimicrobials like ciprofloxacin, ofloxacin, ceftazidime, and cefoperazone. To determine their minimum inhibitory concentration (MIC) is in resistant isolates. Methods: The study was conducted in Bacteriology Laboratory, Department of Microbiology, Government Medical College, Miraj. The design of study: in vitro study on 50 clinical isolates of P. aeruginosa. Results: Among the third generation cephalosporins, ceftazidime (64%) exhibited maximum in vitro activity and among the fluoroquinolones ciprofloxacin (54%) exhibited maximum activity. Out of 50 clinical isolates of P. aeruginosa,17 were resistant to all four antimicrobials,22 were susceptible to all four antimicrobials, and 11 clinical isolates of P. aeruginosa showed mixed susceptibility-resistant pattern. Conclusion: MIC values for resistant strains of P. aeruginosa ranged from 0.03 to 32 µg/ml for fluoroquinolones and 0.5-512 µg/ml for third generation cephalosporins.